Migration and multi-ethnic communities : mobile people from the late middle-ages - Ojala-Fulwood, Maija (De Gruyter, 2018)
This book aims to shed light on a global and complex phenomenon: migration. In order to grasp this vast and ambiguous issue, the book offers ten multi-layered case studies, each focussing on one aspect of migration. With this selection of articles, this collected volume builds a bridge between the past and the present and highlight the many sides of migration. The chapters will demonstrate how the questions of controlled migration, movement of labour, improvement of one's life, and interaction of people of different origin have puzzled us in the course of the last five hundred years.